Does exposure to parasites modify relationships between diurnal cortisol and leukocytes among Honduran women?. Issue 3 (16th August 2020) - Garcia, Angela R.; Trumble, Ben; Kraft, Thomas S.; Murillo, Sergio; Marquez, Mariela; Gurven, Michael; Blackwell, Aaron D.
Abstract: Background: Altered hypothalamic–pituitary–adrenal (HPA) function and related changes in circulating glucocorticoids have been implicated in the pathogenesis of numerous diseases that involve dysregulated immune function. Glucocorticoid hormones have both direct and indirect modulatory effects on both pro‐ and anti‐inflammatory aspects of the immune system, including granulocytic and lymphocytic leukocyte subsets. However, past findings are complicated by inconsistencies across studies in how glucocorticoids and immune markers interact and relate to disease risk. Some incongruencies are likely due to an overreliance on single‐unit (e.g., HPA or one immune marker) measures, and a failure to consider ecological exposures that may shape the base levels or correspondence between these systems. Here, we test single‐unit and diurnal measures of HPA axis and immune system interactions in a less‐industrial ecological setting with relatively high parasite loads. Methods: In a sample of 114 Honduran women (mean age = 36 years), morning and evening blood samples were analyzed to quantify granulocytes, lymphocytes, and immunoglobulin‐E (IgE). Saliva was collected over 2 days (8 samples per woman) to measure peak cortisol, cumulative cortisol, and slope of decline. These repeated measures of saliva and venous blood were used to investigate associations between single‐point and diurnal salivary cortisol and leukocytes, under variable levels of past parasite exposure (proxied by IgE). Results: Individuals with less of a decline in cortisol (i.e., "flatter" decline) show less of an increase in lymphocytes (2.27% increase in cells/μL/hr; 95% CI: 0.91–7.29; p = .01) across the day compared to those with steeper cortisol decline (7.5% increase in lymphocytes; 95% CI: 5.79–9.34; p < .001). IgE levels did not modify this association. Interestingly, IgE did moderate relationships between measures of cortisol and granulocytes: diurnal cortisol was positively associated with granulocytes, only in individuals with high previous exposure to parasites. There were no consistent relationships between single‐unit measures of cortisol, lymphocytes or granulocytes, regardless of past parasite exposure. Discussion: Results demonstrate that the relationship between HPA function and immune modulation cannot be fully understood without an understanding of local disease ecology. These results highlight the importance of research that seeks to identify etiologies of disease across environmental contexts.